Zonulin Family Peptide Levels in Ascites and Serum in Patients with Liver Cirrhosis: A Preliminary Study. (5th November 2019) - Pietrukaniec, Marta; Migacz, Maciej; Żak-Gołąb, Agnieszka; Olszanecka-Glinianowicz, Magdalena; Chudek, Jerzy; Duława, Jan; Holecki, Michał
Abstract : Introduction. Zonulin is a protein that reversibly modulates the permeability of tight junction of the small intestine wall. As the serum concentration of "zonulin family peptides" (ZFPs) is considered to be a sensitive and useful marker of intestinal wall permeability, its serum level may affect the volume of ascites fluid and change in gut microbiota. The aim of the study was to assess the association between concentrations of ZFPs in serum and ascites in relation to the severity of liver cirrhosis. Methods . The preliminary study included 24 adult patients diagnosed with alcoholic or viral liver cirrhosis. 18 healthy adult subjects were enrolled as the control group. In patients and controls, there were measured serum and ascites (only in patients) ZFPs, serum bilirubin, creatinine, alanine aminotransferase, total protein, and C-reactive protein (CRP). Results . Cirrhotic patients had lower serum hemoglobin (11.6 vs. 14.3 mg/dL; p < 0.001 ), platelet count (178 vs. 305 × 10 3 /mm 3 ; p < 0.01 ), total protein and albumin (58.6 vs. 74.3 g/dL; p < 0.001, 26.6 vs. 42.3 g/dL; p < 0.001, respectively), and serum ZFPs (30.5 vs. 62.0 ng/mL; p < 0.001 ) in comparison to controls. In patients with cirrhosis serum bilirubin, C-reactive protein level and INR were higher than in controls (3.07 vs. 0.96 mg/dL; 36.9 vs. 5 mg/L; 1.53 vs. 0.95; p < 0.001, respectively). Patients with low ZFP levels were characterized with lower ascites ZFP levels (0.25 vs. 16.4 ng/mL; p < 0.001 ) and ascites/serum index (0.011 vs. 0.462; p < 0.001 ). There were negative correlations between ascites ZFPs and platelet count (R = − 0.497 ; p < 0.01 ) and positive correlation with INR (R = 0.640 ; p < 0.001 ). ZFP index positively correlated with platelet count (R = 0.726 ; p < 0.001 ) and negatively with INR (R = − 0.392 ; p = 0.06 ). Conclusions . Decrease serum ZFP levels seem to reflect their decreased liver synthesis but not increased gut permeability in patients with liver cirrhosis. The physiologically low level of ZFPs in transudate is increased in exudate.